Abrocitinib monotherapy in Investigator's Global Assessment nonresponders: improvement in signs and symptoms of atopic dermatitis and quality of life. (4th July 2022) - Blauvelt, Andrew; Boguniewicz, Mark; Brunner, Patrick M.; Luna, Paula C.; Biswas, Pinaki; DiBonaventura, Marco; Farooqui, Saleem A.; Rojo, Ricardo; Cameron, Michael C.
Abstract: Background: Abrocitinib, a once-daily, oral Janus kinase 1 selective inhibitor, was shown to be an effective treatment for moderate-to-severe atopic dermatitis in phase 2 b/3 monotherapy trials. Methods: These analyses included data for Investigator's Global Assessment responder (clear [0] or almost clear [1 ] with ≥2-grade improvement) and nonresponder patients with moderate-to-severe atopic dermatitis who received abrocitinib (200 mg or 100 mg) or placebo in three abrocitinib monotherapy trials (phase 2 b, NCT02780167; two phase 3, NCT03349060/JADE MONO-1 and NCT03575871/JADE MONO-2). Outcomes measuring skin clearance, itch, and quality of life were evaluated. Results: Both nonresponders ( n  = 548) and responders ( n  = 260) treated with abrocitinib had rapid and clinically meaningful improvement in skin clearance, itch, and quality of life compared with placebo. Conclusion: Patients with moderate-to-severe atopic dermatitis treated with abrocitinib who did not achieve an Investigator's Global Assessment 0/1 response at week 12 still experienced rapid, clinically meaningful improvements across several other validated measures of efficacy and quality of life. ClinicalTrials.gov: NCT02780167, NCT03349060, NCT03575871